The promise(s) of mesenchymal stem cell therapy in averting preclinical diabetes: lessons from in vivo and in vitro model systems - Nagasuryaprasad Kotikalapudi; Samuel Joshua Pragasam Sampath; Sinha Sukesh Narayan; Bhonde Ramesh R; Harishankar Nemani; Sathish Kumar Mungamuri; Vijayalakshmi Venkatesan (Scientific Reports, 2021)
Abstract Obesity (Ob) poses a significant risk factor for the onset of metabolic syndrome with associated complications, wherein the Mesenchymal Stem Cell (MSC) therapy shows pre-clinical success. Here, we explore the therapeutic applications of human Placental MSCs (P-MSCs) to address Ob-associated Insulin Resistance (IR) and its complications. In the present study, we show that intramuscular injection of P-MSCs homed more towards the visceral site, restored HOMA-IR and glucose homeostasis in the WNIN/GR-Ob (Ob-T2D) rats. P-MSC therapy was effective in re-establishing the dysregulated cytokines. We report that the P-MSCs activates PI3K-Akt signaling and regulates the Glut4-dependant glucose uptake and its utilization in WNIN/GR-Ob (Ob-T2D) rats compared to its control. Our data reinstates P-MSC treatment's potent application to alleviate IR and restores peripheral blood glucose clearance evidenced in stromal vascular fraction (SVF) derived from white adipose tissue (WAT) of the WNIN/GR-Ob rats. Gaining insights, we show the activation of the PI3K-Akt pathway by P-MSCs both in vivo and in vitro (palmitate primed 3T3-L1 cells) to restore the insulin sensitivity dysregulated adipocytes. Our findings suggest a potent application of P-MSCs in  pre-clinical/Ob-T2D management.